(untitled) (International Journal of Engineering and Computer Science, 2025)
One major worldwide health concern is diabetes, a chronic illness marked by high blood glucose levels. Diabetes has always been managed in a traditional manner, but new developments in technology and medical research highlight the necessity of individualized treatment programs to maximize patient outcomes. Individual patient characteristics, including genetic predispositions, lifestyle, health problems, age, and par- ticular glucose metabolism patterns, are taken into consideration in a personalized treatment plan (PTP) for diabetes. This strategy makes it possible to implement specialized interventions, such as food advice, medication schedules, ongoing glucose monitoring, and behavioral changes. Personalized treatments concentrate on reducing problems and enhancing general quality of life in addi- tion to better management. The accuracy of these individualized approaches has been further improved by the incorporation of big data, genetics, and artificial intelligence into diabetes management. The significance of customized treatment plans for diabetes management is emphasized in this abstract, as is their potential to completely transform existing treatment paradigms by offering more efficient and patient-centered care.